Muscarinic Receptors in Cardioprotection and Vascular Tone Regulation - Dolejší, E; Janoušková, A; Jakubík, J (Physiological research, 2024)
Muscarinic acetylcholine receptors are metabotropic G-protein coupled receptors. Muscarinic receptors in the cardiovascular system play a central role in its regulation. Particularly M2 receptors slow down the heart rate by reducing the impulse conductivity through the atrioventricular node. In general, activation of muscarinic receptors has sedative effects on the cardiovascular system, including vasodilation, negative chronotropic and inotropic effects on the heart, and cardioprotective effects, including antifibrillatory effects. First, we review the signaling of individual subtypes of muscarinic receptors and their involvement in the physiology and pathology of the cardiovascular system. Then we review age and disease-related changes in signaling via muscarinic receptors in the cardiovascular system. Finally, we review molecular mechanisms involved in cardioprotection mediated by muscarinic receptors leading to negative chronotropic and inotropic and antifibrillatory effects on heart and vasodilation, like activation of acetylcholine-gated inward-rectifier K+-currents and endothelium-dependent and -independent vasodilation. We relate this knowledge with well-established cardioprotective treatments by vagal stimulation and muscarinic agonists. It is well known that estrogen exerts cardioprotective effects against atherosclerosis and ischemia-reperfusion injury. Recently, some sex hormones and neurosteroids have been shown to allosterically modulate muscarinic receptors. Thus, we outline possible treatment by steroid-based positive allosteric modulators of acetylcholine as a novel pharmacotherapeutic tactic. Keywords: Muscarinic receptors, Muscarinic agonists, Allosteric modulation, Cardiovascular system, Cardioprotection, Steroids.
Keywords: Receptors, Muscarinic; Animals; kardiotonika; Cardiotonic Agents; Vasodilation; lidé; receptory muskarinové; agonisté muskarinových receptorů; Muscarinic Agonists; vazodilatace; Humans; zvířata